Fur love or money - Ryan, Sofie, 1958- (Ryan, Sofie, 1958- Second Chance cat mystery., 2024)
When she and her canine companion stumble upon the dead body of a sticky-fingered financial adviser who swindled millions from investors, Sarah Grayson and Charlotte's Angels, the senior citizen sleuths who work out of her secondhand shop, find the fur flying as they try to untangle the truth.